2011
DOI: 10.1103/physrevlett.106.257201
|View full text |Cite
|
Sign up to set email alerts
|

Computation of Static Heisenberg-Chain Correlators: Control over Length and Temperature Dependence

Abstract: We communicate results on correlation functions for the spin-1/2 Heisenberg chain in two particularly important cases: (a) for the infinite chain at arbitrary finite temperature T, and (b) for finite chains of arbitrary length L in the ground state. In both cases we present explicit formulas expressing the short-range correlators in a range of up to seven lattice sites in terms of a single function ω encoding the dependence of the correlators on T (L). These formulas allow us to obtain accurate numerical value… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(88 citation statements)
references
References 22 publications
3
78
0
Order By: Relevance
“…• Connection to the general theory of short range correlators in the fundamental SU (N )-symmetric models. It is known that in the XXZ and XXX Heisenberg spin chains the mean values of all local operators factorize: they can be expressed as combinations of only a few functions, which originate in the two-site density matrix of an inhomogeneous chain [40,41,42,43]. Our previous work [44,6] showed that for the SU (2)-invariant operators of the homogeneous XXX chain these building blocks are identical to the mean values of the currents J 0 α,β .…”
Section: Discussionmentioning
confidence: 99%
“…• Connection to the general theory of short range correlators in the fundamental SU (N )-symmetric models. It is known that in the XXZ and XXX Heisenberg spin chains the mean values of all local operators factorize: they can be expressed as combinations of only a few functions, which originate in the two-site density matrix of an inhomogeneous chain [40,41,42,43]. Our previous work [44,6] showed that for the SU (2)-invariant operators of the homogeneous XXX chain these building blocks are identical to the mean values of the currents J 0 α,β .…”
Section: Discussionmentioning
confidence: 99%
“…Local correlation function are thus expressible as functionals of the quasi-particle densities characterising a macrostate, see e.g. [46][47][48].…”
Section: Equilibrium Ensemblesmentioning
confidence: 99%
“…An alternative to the TBA is the Quantum Transfer Matrix (QTM) method [33,34], which leads to a single non-linear integral equation replacing the infinite set of the TBA [35]. Moreover, there are very efficient methods available to compute short-range correlations with the QTM [36,37,38]. The simplicity of the QTM with respect to the TBA makes it an excellent candidate to describe the GGE.…”
Section: Introductionmentioning
confidence: 99%